Mitochondrial DNA 8993 (NARP) mutation presenting with a heterogeneous phenotype including 'cerebral palsy'. Issue 5 (November 1994) - Fryer, A; Appleton, R; Sweeney, M G; Rosenbloom, L; Harding, A E
Abstract : The mitochondrial DNA (mtDNA) mutation 8993 is an important cause of Leigh's encephalopathy. A family is reported where other affected members have presented with non-specific delayed development or cerebral palsy. The diagnosis should be considered not only in children with Leigh's encephalopathy, but also in those with mild neurological dysfunction (including cerebral palsy) if there is a pigmentary retinopathy or a family history of neurological or ophthalmological disease. There was some correlation in this family between the disease severity and the proportion of mutant mtDNA in the blood. This mutation appears to segregate to high levels of mutant mtDNA rapidly within pedigrees and the mother of a severely affected child has a high risk of having further children with a high proportion of mutant mtDNA and a severe phenotype.